Effect of Product Quality, Price and Brand Image on The Interest in Buying Products in PT. Onna Prima Utama (Case Study of Onna Banjar Wijaya Interior Tangerang Branch) - Septian Tjahyadi (Komunitas Dosen Indonesia, 2022)
This study aims to analyze the influence of product quality, price, and brand image in a similar manner on consumer buying interest in Onna products. This research population is consumers who use Onna products through Banjar Wijaya Interior. The total population in Banjar Wijaya Interior is 132 people. The data collection techniques used in this study used primary data. Where data collection is done through survey methods using questionnaires. Questionnaires are given directly to respondents. The study distributed questionnaires to 100 consumers with a total of 40 questions. The results of this study showed that, product quality does not have a significant effect on buying interest, price does not have a significant effect on buying interest, brand image has a significant effect on buying interest and product quality, price and brand image simultaneously have a significant effect on buying interest. The results of this research are expected to be a contribution of thought used for consideration for companies regarding the importance of product influence, price, and brand image on consumer buying interests. For consumers, it is expected that consumers can assess things that must be considered from various factors when they want to buy a product both in the form of goods and services. For further researchers, it is hoped that the next study can look for and add other variables that affect buying interest so that the results of the study are more adequate